Clinical and Biomedical Research: Positive prospects for the journal - Zavascki, Alexandre Prehn (Clinical and Biomedical Research, 2014)
It is a great pleasure to present the second issue of Clinical and Biomedical Research and some of our work toward setting new standards for the journal. This issue contains two review articles, eight original articles, and four case reports, covering a wide range of topics important to the practice of medical sciences.